PEMBELAJARAN MENULIS CERITA PENDEK MENGGUNAKAN MODEL EXAMPLE NON EXAMPLE PADA SISWA KELAS IX - Mutiari Habilah; Teti Sobari; Enung Nurhayati (IKIP Siliwangi, 2020)
This research is motivated by the low ability and interest of students in writing, especially writing short stories. Writing itself is a creative process of transferring ideas or ideas into writing that is systematic and easy to understand. Factors for the occurrence of these problems can be caused by factors teachers and students who have an important role in achieving a learning goal. Therefore, researchers try to overcome these problems by growing student interest so that the ability to write short story texts can be improved. In general, the objectives in this study are to illustrate: (1) The application of the non example example model to learning to write short story text in grade IX students, and (2) The effectiveness of using the example non example model to the ability of grade IX students in writing short story text. In this research the method used is descriptive qualitative. Data collection is obtained through observation, tests and interviews. The subjects in this study were the teacher and class IX students, amounting to 21 students. Based on the results of this study indicate that (1) Students are able to follow the learning activities of short story texts well using the model example non example. (2) Based on the results of the final test the ability to write short story texts for class IX students is classified as good with the acquisition of the final average score of students is 75.04, so it can be said that the use of example non example models is effectively used in writing short story texts.